Performing the virtual double - Amanda du Preez (Communicare)
In what follows the idea of the online double is historically contextualised and analysed. Beginning with the contemporary idea of the ‘selfie’ as online self-induced double, I proceed to discuss the Doppelgänger’s (double) mythical and literary roots, in order to expand the discussion of the selfie to include the online double. Two instances of the online double are unpacked, namely the double as shadow and the double as a stand-in or alter-ego, which correspond significantly with Marshall McLuhan’s analysis of the Narcissus myth and technological use. McLuhan reveals the doubled nature of our technological engagement that leads to either self-amputation or self-amplification. In my analysis, the double as shadow is correlated with self-amputation and the double as alterego with self-amplification. It is argued that the double as shadow is evoked online through the mining of data regarding the self that is captured consciously and unconsciously to create what is known as the Data Doppelgänger. The figure of the Doppelgänger is further vividly conjured through virtual stand-ins or alter-egos that act on behalf of the self to create a tele-presence through examples such as Project Lifelike and rep.licants.org.